2004
DOI: 10.1002/jgm.615
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting dendritic cells for cancer immunotherapy: genetic modification of dendritic cells

Abstract: Dendritic cells (DCs) are pivotal regulators of immune reactivity and immune tolerance. The observation that DCs can recruit naive T cells has invigorated cancer immunology and led to the proposal of DCs as the basis for vaccines designed for the treatment of cancer. Designing effective strategies to load DCs with antigens is a challenging field of research. The successful realization of gene transfer to DCs will be highly dependent on the employed vector system. Here, we review various viral and non-viral gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 167 publications
(134 reference statements)
0
35
0
Order By: Relevance
“…Our study not only confirms these observations, but provides substantial additional information. First, adenovirus infection renders the DCs more mature and more immunogenic, whereas lentiviral transduction has no such effect [40]. Feili-Hariri et al reported an enhanced CD40, CD80 and CD86 expression, while these markers, as well as MHC class II, were not or minimally changed in our case.…”
Section: Discussionmentioning
confidence: 50%
“…Our study not only confirms these observations, but provides substantial additional information. First, adenovirus infection renders the DCs more mature and more immunogenic, whereas lentiviral transduction has no such effect [40]. Feili-Hariri et al reported an enhanced CD40, CD80 and CD86 expression, while these markers, as well as MHC class II, were not or minimally changed in our case.…”
Section: Discussionmentioning
confidence: 50%
“…RNA encoding the immunoreceptors was transferred to T cells by electroporation, which is a vector-independent transfer system. RNA electroporation initially was used to modify dendritic cells to express tumor antigens 30,31 or to functionally manipulate these cells. 32,33 Subsequently, RNA electroporation was used to transfer full-length TCR to T cells to redirect them with a new specificity.…”
Section: Discussionmentioning
confidence: 99%
“…1-3). Several strategies have been developed to deliver TAAs to DCs, including the use of mRNA (4)(5)(6). Autologous DCs loaded ex vivo with TAA mRNA have been extensively tested in preclinical studies, showing their ability to induce functional T H 1 cells and CTLs (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%